Evaluation of Anti-inflammatory Effects of Steroids and Arthritis-Related Biotherapies in an In Vitro Coculture Model with Immune Cells and Synoviocytes - Noack, Mélissa; Ndongo-Thiam, Ndiémé; Miossec, Pierre (Frontiers in Immunology, 2016)
Background: During rheumatoid arthritis (RA), steroids and biotherapies are used alone and combined. Efficacy has been established in clinical trials but their differential effects at the cellular level are less documented. The aim was to study these cellular effects using an in vitro model with synoviocytes interacting with peripheral blood mononuclear cells (PBMC) to reproduce the interactions in the RA synovium. Methods: Activated-PBMC were co-cultured with RA synoviocytes during 48h. A dose-response of methylprednisolone (MP) was tested and different biotherapies (Infliximab, Etanercept, Adalimumab, Tocilizumab, Abatacept and Rituximab) were added alone or in combination with MP. Cytokine production (IL-17, IL-6, IL-1β, IFN-γ and IL-10) was measured by ELISA. Results: Addition of MP to co-cultures inhibited the production of all cytokines. The response to the biotherapies alone was treatment-dependent. IL-17 production was inhibited only by Tocilizumab (p=0.004) while IL-6 was decreased only by Infliximab (p≤0.002). IL-1β level was affected in all conditions (p≤0.03). IFN-γ production was mainly decreased by Infliximab (p=0.004), and IL-10 by Infliximab and Tocilizumab (p≤0.004). The combination MP and biotherapy did not induce an additional effect on pro-inflammatory cytokine inhibition. The combination MP and biotherapies induced a higher IL-10 secretion than MP alone, mainly with Rituximab. Conclusion: Steroids inhibited the secretion of all cytokines, and low doses were as potent. The anti-inflammatory effect of biotherapies was dependent on their mechanism of action. MP and biotherapy combination did not enhance the inhibitory effect on pro-inflammatory cytokines but could have a beneficial effect by increasing IL-10 production.